Determinants of mental health professionals’ attitudes towards recovery: a review - Luigi, Mimosa; Rapisarda, Filippo; Corbière, Marc; De Benedictis, Luigi; Bouchard, Anne-Marie; Felx, Amélie; Miglioretti, Massimo; Abdel-Baki, Amal; Lesage, Alain (Canadian Medical Education Journal, 2020)
Objective: The attitudes of mental health professionals towards consumers’ recovery are far more pessimistic than what is needed for the recovery-orientation to truly permeate systems of care. It has become pressing to depict determinants for these attitudes and how they evolve during professionalization. This, in the hopes to adjust not only medical education, but also ongoing training of professionals. Methods: A systematic search of PubMed and PsycINFO databases was conducted, yielding a net 15 303 records. Twenty-two publications from specific educational journals and reference lists were added. Finally, thirty-four full texts were read, from which twenty-two articles were included. Results: From the reviewed studies emerged five main determinants: profession, education, age, clinical experience, and nature of the contact with consumers. Traditional clinical placements during residency, negative experiences with acute patients, younger age and the professional attitudes of psychiatrists seem to all be determining factors for professionals’ pessimistic attitudes towards recovery. Conclusions: This review found specific determinants for attitudes in recovery and four out of five can be acted upon. For a recovery-orientation to be implemented across our mental health system, we formulate recommendations within the Canadian context for revision of curriculum, recovery-specific training, and operationalisation through state/provincial technical assistance centers.